PENGETAHUAN TENTANG PERAWATAN KAKI DENGAN PRAKTIK PERAWATAN KAKI DIABETIK PADA PENDERITA DIABETES MELITUS - Hidayati, Yuli; Pratama, Kharisma; Wahyudi, Ardi (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Diabetes mellitus is one of the major non-communicable diseases with high prevalence and severe complications, such as diabetic foot ulcers, which may lead to amputation. Preventive efforts through proper foot care largely depend on patients’ knowledge levels. Objective: This study aimed to determine the relationship between knowledge level and foot care practices among patients with diabetes mellitus in the working area of Sungai Baru Public Health Center, Teluk Keramat District, Sambas Regency. Methods: This research employed a quantitative correlational design with a survey approach involving 44 respondents selected using Proportionate Stratified Random Sampling. Data were collected using the standardized Diabetes Foot Knowledge Questionnaire and the Nottingham Assessment of Functional Footcare. Data analysis was performed using the Chi-Square test with a 95% confidence level. Results: Most respondents were under 55 years old (65.9%), female (54.5%), had elementary education (38.6%), and earned below Rp2,792,599 (93.2%). A total of 61.4% of respondents had good knowledge, and 54.5% had good foot care practices. The Chi-Square test showed a significant relationship between knowledge and diabetic foot care practices (p=0.00). Conclusion: There is a significant correlation between knowledge and foot care practices among diabetes mellitus patients. Continuous health education and nurse-led assistance are essential to improve self-care behaviors and prevent diabetic foot ulcers.